Bis(bipyridine)ruthenium(II) Ferrocenyl β‐Diketonate Complexes: Exhibiting Nanomolar Potency against Human Cancer Cell Lines - Allison, Matthew; Caramés‐Méndez, Pablo; Pask, Christopher M.; Phillips, Roger M.; Lord, Rianne M.; McGowan, Patrick C. (Chemistry : a European journal, 2021)
The synthesis and characterization of new bis(bipyridine)ruthenium(II) ferrocenyl β‐diketonate complexes, [(bpy)2Ru(Fc‐acac)][PF6] (bpy=2,2′‐bipyridine; Fc‐acac=functionalized ferrocenyl β‐diketonate ligand) are reported. Alongside clinical platinum drugs, these bimetallic ruthenium‐iron complexes have been screened for their cytotoxicity against MIA PaCa‐2 (human pancreatic carcinoma), HCT116 p53+/+ (human colon carcinoma, p53‐wild type) and ARPE‐19 (human retinal pigment epithelial) cell lines. With the exception of one complex, the library exhibit nanomolar potency against cancerous cell lines, and their relative potencies are up to 40x, 400x and 72x more cytotoxic than cisplatin, carboplatin and oxaliplatin, respectively. Under hypoxic conditions, the complexes remain cytotoxic (sub‐micromolar range), highlighting their potential in targeting hypoxic tumor regions. The Comet assay was used to determine their ability to damage DNA, and results show dose dependent damage which correlates well with the cytotoxicity results. Their potential to treat bacterial and fungal strains has been determined, and highlight complexes have selective growth inhibition of up to 87–100 % against Staphylococcus aureus and Candida albicans. Hetero‐bimetallic ruthenium(II)‐ferrocenyl complexes with nanomolar potency towards cancer cell lines, which retain their activity in hypoxic conditions, show dose‐dependent DNA damage and are active inhibitors of bacterial and fungal strains.